Patient 'follow up' as a pedagogical technique for medical students (Res Medica, 2013)
Medicine is a career that requires lifelong learning, and finding an effective way of doing this is a valuable skill to have acquired as a medical student. ‘Follow up’ is a normal part of the treatment process for patients where most doctors see their patients in clinic post-discharge. This is beneficial for the patient, who receives a high quality continuum of care, and for the doctor, who can further their knowledge of pathological progression and individual responses to treatment. Medical students do not seem to regularly chase patient results or seek to find out clinical outcomes, despite students at some hospitals having access to electronic patient records systems.Pedagogy is the science of teaching and education. There is little evidence of the use of ‘follow up’ as a pedagogical technique, but there are some obvious gains to be made from doing so, including acquiring skills in using specific hospital computer systems, appreciating the holistic nature of medical care and laying down strong foundations of clinical experiences, which can be built on with personal study. There are ethical issues surrounding patient confidentiality where students have access to personal records, but as long as governance guidelines are followed the benefits of the ‘follow up’ process outweigh any potential risk to patient confidentiality. There are multiple benefits to following up a patient, and it is a practice that more medical students should embark upon.